Sources of Predictability of European Stock Markets for High-Technology Firms - Christian Pierdzioch; Andrea Schertler (Kiel Institute for World Economics (IfW), 2005)
We study return predictability of stock indexes of blue chip firms and smaller hightechnology firms in Germany, France, and the United Kingdom during the second half of the 1990s. We measure return predictability in terms of first-order autocorrelation coefficients, and find evidence for return predictability of stock indexes of smaller hightechnology firms, but no evidence for return predictability of stock indexes of blue chip firms. Our findings suggest that a leading candidate for explaining the economic sources of return predictability of stock indexes of smaller high-technology firms is transaction costs.
Keywords: N24; G14; 330; Stock markets; Return predictability; High-technology firms; Kapitalertrag; Börsenkurs; Prognoseverfahren; Autokorrelation; Schätzung; Hochtechnologiesektor; Deutschland; Frankreich; Grossbritannien